Comparison of the efficacy of alginate nanoparticles containing Cymbopogon citratus essential oil and citral on melanoma and breast cancer cell lines under normoxic and hypoxic conditions - Farnaz Karami; Mahmoud Osanloo; Hiva Alipanah; Elham Zarenezhad; Fatemeh Moghimi; Ali Ghanbariasad (BMC, 2024)
Abstract Background Solid tumors often develop hypoxic regions, leading to aggressive behavior and increased drug resistance. Methods The chemical composition of Cymbopogon citratus essential oil (EO) was analyzed using GC-MS. Alginate nanoparticles containing the EO and its primary component, citral, were synthesized via the ionic gelation method. Encapsulation was confirmed using ATR-FTIR analysis. The anticancer efficacy of C. citratus EO, citral, and their respective alginate nanoparticles was evaluated under normoxic (21% oxygen) and hypoxic (1% oxygen) conditions on breast cancer (MDA-MB-231) and melanoma (A-375) cell lines. Additionally, qPCR and flow cytometry were used to assess apoptosis gene expression ratios (Bax/Bcl-2) and levels of apoptosis. Results Citral (80.98%) was identified as the major component of the EO. Alginate nanoparticles containing C. citratus EO and citral (C. citratus-AlgNPs and citral-AlgNPs) were synthesized with particle sizes of 195 ± 4 nm and 222 ± 9 nm, and zeta potentials of -22 ± 3 mV and − 17 ± 1 mV, respectively. Both samples demonstrated significantly greater efficacy under hypoxic conditions. Citral and C. citratus-AlgNPs had IC50 values of 27 (19-39) µg/mL and 25 (4-147) µg/mL, respectively, against MDA-MB-231 and A-375 cells. Flow cytometry showed increased apoptosis under hypoxic conditions, with the highest rates observed for citral-AlgNPs and C. citratus-AlgNPs (84 ± 5 and 92 ± 5% in MDA-MB-231 and A-375 cells, respectively). Conclusion This study demonstrates that alginate nanoparticles enhance the anticancer activity of C. citratus-AlgNPs and citral, particularly under hypoxic conditions, highlighting their potential for hypoxia-targeted cancer therapies.